2019
DOI: 10.1103/physrevapplied.12.064052
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Doping of Organic Semiconductors to Enhance Carrier Injection

Abstract: If not oriented perfectly isotropically, the strong dipole moment of polar organic semiconductor materials such as tris-(8-hydroxyquinolate)aluminum (Alq 3) will lead to the buildup of a giant surface potential (GSP) and thus to a macroscopic dielectric polarization of the organic film. Despite this having been a known fact for years, the implications of such high potentials within an organic layer stack have only been studied recently. In this work, the influence of the GSP on hole injection into organic laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…Recently, Hofmann et al, reported a method suitable for modifying the injection barrier into the HTL using the concept of dipolar doping. [129] For this purpose, a former unpolar molecule like NPB is doped with the polar species Alq 3 , which leads to a tunable GSP in the respective layer. [113,129] Although the doped HTL shows lower mobility, a reduction of the interface dipole at the anode/NPB:Alq 3 interface leads to an overall lower injection barrier, with currents increasing by one order of magnitude at low doping ratios.…”
Section: Additional Influence Of a Gsp On Charge Injectionmentioning
confidence: 99%
“…Recently, Hofmann et al, reported a method suitable for modifying the injection barrier into the HTL using the concept of dipolar doping. [129] For this purpose, a former unpolar molecule like NPB is doped with the polar species Alq 3 , which leads to a tunable GSP in the respective layer. [113,129] Although the doped HTL shows lower mobility, a reduction of the interface dipole at the anode/NPB:Alq 3 interface leads to an overall lower injection barrier, with currents increasing by one order of magnitude at low doping ratios.…”
Section: Additional Influence Of a Gsp On Charge Injectionmentioning
confidence: 99%
“…Secondly, already a small degree of orientational ordering, obtained upon thermal evaporation deposition, can lead to a large net dipole moment of a layer ["giant surface potential" (GSP) or "spontaneous orientation polarization" (SOP) effect]. This modifies the electric * r.coehoorn@tue.nl field across the device thickness, affects charge injection from an electrode and transport across internal interfaces [9][10][11][12][13][14][15], can lead to an enhanced exciton dissociation rate [16], and can already below the turn-on voltage lead to enhanced exciton quenching due the interaction with accumulated charges at the interface between an emissive layer and a charge transport layer with a large GSP effect [17]. Finally, phosphorescent emitter molecules with large static dipole moments that are present at small concentrations in a blend show a tendency to aggregate during thin-film deposition, leading to a red-shifted emission and to an enhanced efficiency loss due to triplet-triplet annihilation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, SOP induces a significant amount of polarization charge on the heterointerfaces of the stacked multilayered OLEDs. Consequently, SOP can modify the interfacial properties of the device, such as the charge injection, accumulation, and recombination 2,5,7–9 . We need to design the device structure and analyze the device characteristics by taking into account the presence of SOP.…”
Section: Introductionmentioning
confidence: 99%